Bissu on Contesting Indigeneity with Islamic Puritanism in the Sacred Arena - Suheri Suheri; Rabiatul Adawiah; Ahmed Sarjoon Razick; Hasse Jubba (UIN Sunan Kalijaga Yogyakarta, 2021)
The presence of Islam in the Bugis Bone tribe not only changes people's beliefs but also traditional activities such as wedding rituals, mappalili (traditional ceremonies before planting rice), guarding arajang (heirlooms). The positions of Bissu, who is an indigenous leader, are very influential in the Bugis Bone community, but nowadays, its existence is discredited by the presence of Islamic hegemony. This research focuses on the transformation of the perseverance of Bissu in the leadership of traditional rituals in the Bugis Bone Tribe, before and after interacting with Islamic religious values. This study uses a descriptive method that describes the social conditions in the life of Bissu, by observation and interview techniques to the Bissu, Muslim leaders, and cultural actor. This study found the fact that the existence of Islam had a dominant influence on the social status of Bissu, which resulted in their role as leaders of traditional rituals being less respected by the community. The role of Bissu in daily activities has become less involved because it has been replaced by the values of religious puritanism. The government needs to educate the history of Bissu and the cultural traditions of Bone to the public and young generation.